2014
DOI: 10.1097/scs.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Free Fibular Flaps With Reamer-Irrigator-Aspirator Bone Grafts for the Reconstruction of Critical-Sized Mandibular Defects

Abstract: The RIA technique significantly reduces operative time and provides bone of equal strength and histologic quality to FF flap reconstruction in a large animal model. The RIA method may represent an efficient technique for the reconstruction of craniomaxillofacial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Full‐text copies of 54 manuscripts were retrieved. Data was not retrieved from 37 of the 54 full‐text papers for meeting the following exclusion criteria; not using free flaps ( n = 2), not reporting a failure rate ( n = 7), using only 1 free flap harvest site ( n = 6), using an uncommon combination of free flaps ( n = 1), studying cadavers ( n = 1), studying animals ( n = 1), not reporting at least 1 failure ( n = 18), or containing data from another larger study ( n = 1) . Seventeen studies underwent data extraction and are reported in Table …”
Section: Resultsmentioning
confidence: 99%
“…Full‐text copies of 54 manuscripts were retrieved. Data was not retrieved from 37 of the 54 full‐text papers for meeting the following exclusion criteria; not using free flaps ( n = 2), not reporting a failure rate ( n = 7), using only 1 free flap harvest site ( n = 6), using an uncommon combination of free flaps ( n = 1), studying cadavers ( n = 1), studying animals ( n = 1), not reporting at least 1 failure ( n = 18), or containing data from another larger study ( n = 1) . Seventeen studies underwent data extraction and are reported in Table …”
Section: Resultsmentioning
confidence: 99%